2021
DOI: 10.1523/jneurosci.1787-20.2021
|View full text |Cite|
|
Sign up to set email alerts
|

Dorsal Root Ganglia Macrophages Maintain Osteoarthritis Pain

Abstract: Pain is the major debilitating symptom of osteoarthritis (OA), which is difficult to treat. In OA patients joint tissue damage only poorly associates with pain, indicating other mechanisms contribute to OA pain. Immune cells regulate the sensory system, but little is known about the involvement of immune cells in OA pain. Here, we report that macrophages accumulate in the dorsal root ganglia (DRG) distant from the site of injury in two rodent models of OA. DRG macrophages acquired an M1-like phenotype, and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 64 publications
5
46
0
Order By: Relevance
“…For example, macrophage accumulation in the dorsal root ganglia appears to mediate pain in mouse models of osteoarthritis. 14 These results suggest novel therapeutic strategies for KOA will require the modulation or prevention of inflammation which could be of value for postmenopausal patients.…”
Section: Inflammationmentioning
confidence: 98%
“…For example, macrophage accumulation in the dorsal root ganglia appears to mediate pain in mouse models of osteoarthritis. 14 These results suggest novel therapeutic strategies for KOA will require the modulation or prevention of inflammation which could be of value for postmenopausal patients.…”
Section: Inflammationmentioning
confidence: 98%
“…The deletion of CCR2 was also shown to inhibit the DRG macrophage infiltration and reduce pain-related behaviors ( 166 , 167 ). Recently, Raoof et al ( 193 ) reported in rat models of OA (MIA and Groove surgery induced OA), that DRG macrophages display an M1-like proinflammatory phenotype, and systemic or local depletion of DRG macrophages reduce OA pain without affecting the pathology ( 193 ). Moreover, the inhibition of M1-like macrophages in DRG through intrathecal administration of an IL4-IL10 fusion protein or M2-like macrophages also reduced OA pain ( 193 ).…”
Section: The Neuroimmune Crosstalk In Joint Disordersmentioning
confidence: 99%
“…Tewari et al ( 190 ) showed that the conditioned medium from NGF-stimulated nociceptors modified macrophages gene transcription, upregulating the expression of inflammatory mediators and chemokines, such as IL-1β, IL6, and CCL22 ( 190 ). Moreover, it was shown, in an in vitro experiment, that sensory neurons that innervate the OA knee joint in the rat polarize DRG macrophages into an M1-like phenotype ( 193 ).…”
Section: The Neuroimmune Crosstalk In Joint Disordersmentioning
confidence: 99%
“…Evidence from preclinical and clinical studies has suggested that the presence of macrophages in the joints and DRGs, direct or indirectly contributes to the generation and maintenance of pain in OA (for a review, see ( Geraghty et al, 2021 )). In murine models of OA, macrophage depletion has been associated with reduction of OA symptoms, including osteophyte formation ( Blom et al, 2004 ) and pain ( Raoof et al, 2021 ). In a clinical study, activated macrophages found in 76% of OA knee, were associated with OA pain severity and radiographic OA severity ( Kraus et al, 2016 ).…”
Section: Sex Differences and Innate-immunity-related Oa Pain Mediatorsmentioning
confidence: 99%
“…Differences in macrophage phenotype also appears to contribute to the OA pathogenesis and studies in this direction have been conducted ( Wood et al, 2019 ; Chou et al, 2020 ), although further investigation is needed. In addition to the synovium and synovial fluid, DRG macrophages have also been described to contribute to both the initiation and persistence of OA pain ( Raoof et al, 2021 ). However, whether these mechanisms in which macrophages are involved in OA pain are different between men and women is unknown.…”
Section: Sex Differences and Innate-immunity-related Oa Pain Mediatorsmentioning
confidence: 99%